Sistem Pemerintahan Negara Al-Ahkam As Shulthaniyah serta Relevansinya di Indonesia - Alfan Khairul Ichwan (Universitas Jember, 2022)
AbstractAl-Mawardi in the book Al-ahkam As-Shulthaniyah explains about the types of state administration that have a relationship between religion and the state. First, the type of state that uses the Ahl Al-Hall wa al-Aqdi system in its concept of application, this type of state uses a lot of deliberation systems to appoint or vote, which is widely used by the government system (Khilafah). The formulation of the problem is how is the deliberation system suitable to be applied in Indonesia? How is the system of government in the book of Al-ahkam As Shulthaniyah and its application in several countries? How is the relevance of Ahl Al-Hall wa al-Aqli Kitab Al-ahkam As Shulthaniyah and its relevance to government in Indonesia?The method in this writing uses a comparative legal study approach (Comparative Approach). The next approach is carried out using a historical study (Historical Approach). The government system contained in Alahkam Ashulthaniyah has become a miniature system that has high democratic values. The government system in Alahkam Asshulthaniyah has the same values ​​as the government system in Indonesia, including the nomination stage system for heads of state.Keyword: Keywords: state government system, Al Ahkam Ashultahaniyah, government system in Indonesia